Industry-mandated testing to improve food safety: the new US marketing order for pistachios - Henrich Brunke; Julian M. Alston; Richard S. Gray; Daniel A. Sumner (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2004)
Food safety shocks can threaten the health of consumers, create havoc within an industry and result in severe losses to producers. Governments often attempt to aid food safety by mandating standards and inspection of food products to supplement the efforts by private firms and industries. This article assesses a form of collective action that falls between typical government mandates and purely private action. The California pistachio industry recently established a U.S. federal marketing order, which sets quality standards and inspection to reduce the likelihood of dangerous or poor quality pistachios. Simulation results indicate that, across the full range of parameters used in the analysis, the benefit-cost analysis was always favorable to the new policy. In the case of California pistachios, collective action is likely to be a helpful tool to ensure a safe product and increase benefits to producers and consumers. – – Lebensmittelskandale bedrohen nicht nur die Gesundheit des Verbrauchers, sondern verursachen oft auch enorme Verluste bei den Produzenten. Zusätzlich zu Initiativen von Firmen und Wirtschaftszweigen versuchen Regierungen, den Verbraucherschutz durch Produktstandards und Qualitätskontrollen zu gewährleisten. Dieser Artikel untersucht eine Form des kollektiven Handelns, die zwischen Aktivitäten einzelner Firmen und den Handlungen der Regierung angesiedelt werden kann. Die kalifornische Pistazienindustrie hat vor kurzem unter nationalem Recht eine Vermarktungsverordnung eingeführt, die durch Qualitätsstandards und Kontrollen das Vorkommen gesundheitsschädlicher und minderwertiger Pistazien reduzieren soll. Simulationsergebnisse zeigen, dass über das gesamte Spektrum der in der Analyse verwendeten Parameter eine Nutzen-Kosten-Analyse immer positive Nettoeffekte ergab. Kollektives Handeln erscheint daher als ein nützliches Instrument für die Vermarktung eines gesunden Produktes mit positiven Wohlstandseffekten für Produzenten und Konsumenten. (Quelle: Verlag)
Keywords: 330; Pistazien; Lebensmittelsicherheit; Ernährungsindustrie; Kosten-Nutzen-Analyse; Kalifornien